Financing global climate change mitigation - United Nations. Economic Commission for Europe (New York ; Geneva : United Nations, 2010)
This publication addresses the massive investments that will be requ ired in addition to the mobilization of substantial new financial resou rces that will be needed in order to continue the fight on global clima te change. The first part provides a review of the existing mechanisms that channel funds to energy efficiency and renewable energy (EERE) pr ojects and understand the success factors in designing EERE financing m echanisms. The second provides a review of the technical, economic, an d regulatory conditions in each region and a summary of main activities undertaken by national governments and international institutions, wit h a particular regard to the work of the UN regional commissions.--Publ isher's description.
Includes bibliographical references
Keywords: Climatic changes -- Economic aspects; Renewable energy sources